Aspectos para uma história crítica da Análise: analítica kantiana e lagrangiana (Revista Eletrônica Estudos Hegelianos, 2016)
The present article aims at bringing to light some aspects of Kant’s and Joseph-Louis Lagrange’s conceptions of analysis. The importance of observing the difference between these two concepts of analysis is evidenced in the realization that these are two necessary conditions to understand the radical criticism operated by Hegel against the arithmetic-symbolic model of analysis rooted in Leibniz. We consider such themes to be of key importance not only to what concerns the clarification of questions related to German Idealism, but especially to what concerns the inquiry about the pre-history of the concept of mathematical analysis which was to achieve its crowning in the second half of the 19th century thus setting the ground for the philosophical perspective which in the first decades of the 20th century established itself as Analytic Philosophy. What we aim,therefore, is to present some of the aspects of the Hegelian thesis concerning the historical necessity of the selfovercomingof the analysis (arithmetical-symbolic) into the dialectics (conceptual-speculative).